2011
DOI: 10.1002/pd.2733
|View full text |Cite
|
Sign up to set email alerts
|

First trimester pregnancy‐associated plasma protein‐A in pregnancies complicated by subsequent gestational diabetes

Abstract: First trimester PAPP-A concentrations were lower among pregnant women with subsequent gestational diabetes than in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 37 publications
8
48
0
4
Order By: Relevance
“…There were, however, only two (1.2%) women with GDM in our study who required insulin, a much lower frequency compared with other study populations (12%-100%). 8,9,11,18,23,[26][27][28][29] Although both women had a lower PAPP-A MoM than women with non-insulin-treated GDM or non-GDM group, such a small proportion is insufficient to determine whether PAPP-A MoM differs significantly between women with insulin-treated GDM and non-insulintreated women with GDM. The low frequency of insulin treatment in our study population may imply that the majority of affected Chinese women had mild GDM and may also explain why our study population did not exhibit changes in PAPP-A MoM during the first trimester.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There were, however, only two (1.2%) women with GDM in our study who required insulin, a much lower frequency compared with other study populations (12%-100%). 8,9,11,18,23,[26][27][28][29] Although both women had a lower PAPP-A MoM than women with non-insulin-treated GDM or non-GDM group, such a small proportion is insufficient to determine whether PAPP-A MoM differs significantly between women with insulin-treated GDM and non-insulintreated women with GDM. The low frequency of insulin treatment in our study population may imply that the majority of affected Chinese women had mild GDM and may also explain why our study population did not exhibit changes in PAPP-A MoM during the first trimester.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with the results of three other studies 18,26,27 but contradicts others. 8,9,11,23,28,29 These published series are summarised in Table 5. 8,9,11,18,23,[26][27][28][29] There are several possible explanations for the different results of these studies, including ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study, of a small number of cases, 7 showed a significant reduction in both concentrations of PAPP-A and free hCG, whilst other studies 12,18 found either no significant effect or found a significant reduction only for PAPP-A. 19 The current study aims to investigate whether the presence of confirmed GDM has any impact on the first trimester aneuploidy screening markers foetal nuchal translucency (NT), maternal serum free hCG or PAPP-A.…”
Section: Introductionmentioning
confidence: 99%
“…2013 yılında İtalya'da yapılan bir araştırmada, serum PAPP-A değerlerinin gestasyonel diyabet ile ilişkisi araştırılmış ve düşük PAPP-A değerlerinin gestasyonel diyabet ile ilişkisi istatistiksel olarak güçlü bulunmuştur (17) . 2011 yılında yayınlanan bir başka çalış-mada, ilk trimester düşük PAPP-A seviyelerinin gelişebilecek gestasyonel diyabet ile ilişkisi gösteril-miştir (18) . Pedersen ve ark.…”
Section: Discussionunclassified